Biofilm Formation, Pyocyanin Production, and Antibiotic Resistance Profile of Pseudomonas aeruginosa Isolates from Wounds - Larissa Yetendje Chimi; Michel Noubom; Borel Ndezo Bisso; Guy Sedar Singor Njateng; Jean Paul Dzoyem (International Journal of Microbiology)
Pseudomonas aeruginosa is one of the most frequently resistant and dangerous bacteria isolated from infected wounds of patients. This study aimed to determine the prevalence of P. aeruginosa from infected wounds of patients in the Dschang District Hospital to evaluate their antibiotic susceptibility profiles and their ability to swarm and swim and correlate pyocyanin production with biofilm formation. Wound swab samples were collected and the identification of P. aeruginosa was performed using microbiological and biochemical tests. Their antimicrobial susceptibility was determined by the broth microdilution method. Swarming and swimming were determined by measuring the diameters of motility in semisolid/low-viscosity media. Furthermore, pyocyanin production and biofilm formation were evaluated spectrophotometrically using a microtiter plate. The prevalence of P. aeruginosa from infected wounds in our study population was 26%. All P. aeruginosa isolates were resistant to streptomycin and paromomycin, and the frequency of multidrug resistance (MDR) was 65.8%. All P. aeruginosa isolates showed the ability to produce biofilm and pyocyanin. Out of the 37 isolates screened, 19 including the reference strains (51.4%) were strong biofilm producers. A significant positive correlation was observed among biofilm formation, pyocyanin production, and the antibiotic resistance profile of the isolates. Findings from this study suggest that infected wounds could act as a reservoir for MDR and virulent P. aeruginosa. The presence of strong biofilm producers of P. aeruginosa in infected wounds is a serious public health concern. Therefore, surveillance programs to monitor and control MDR P. aeruginosa in these patients are required to prevent their dissemination in hospital settings.